Ciri Morfologi Polen Dan Spora Tumbuhan Dari Sedimen Rawa Jombor Klaten - Sarah, Solifa; Agung Suedy, Sri Widodo; Hastuti, Endah Dwi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
The Marsh of Jombor Klaten is a natural swamp that was once small swamps surrounded by villages and hills located in the lower mainland and serves to hold rainwater. Environmental has changed from the lowlands into the aquatic environmentand the more widespread the diversity of types of flora around the Swamp Jombor has been changed.The diversity of types of flora can be known through the morphology of the pollen and spores. The purpose of this research is to know the diversity of plant species based on morphology of pollen and spores found in Swamp sediment Jombor. Sampling is done by drilling sedimentary soil clays Swamp Jombor on three points with the first location code RWJ (3) at a depth of 2 m situated around the keramba, the second code RWJ (4) at a depth of 1.5 m, and third code RWJ (5) at a depth of 0.35 m located around the inlet.The sample preparation using method asetolisis, then morphological characteristics observed pollen and spores. Calculated the number of each type of pollen and spores.The data obtained were analyzed using pollen and spore morphology of description. The data obtained were analyzed using pollen morphology characteristics and description of the spores found in the swamp Jombor. The results showed that the morphology of the pollen and spores found in Swamp sediment Jombor has a variation of shapes and sizes. The flora type obtained from the sediments Swamp Jombor as much as 28 type, including 8 typearboreal pollen (AP), 9 typenon arboreal pollen (NAP), and 11 type of spores. Types of flora that dominates is the NAP family Gramineae (80,10%) which indicates the plant a tree instead of in the form of shrubs or herbaceous were more developed in marsh of Jomborenvironment.Â Keywords: Jombor, morphology, pollen, spore, diversity.